PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS XII IPA-2 SMA NEGERI 1 BAGAN SINEMBAH KAB. ROKAN HILIR - Dalima Siregar (PGSD Universitas Negeri Medan, 2018)
The purpose of this study was to determine the improvement of science process skills and student learning outcomes after the application of a guided curriculum learning model in class XII IPA-2 State Senior High School 1 Bagan Sinembah District. Rokan Hilir. This research was carried out in the classroom including classroom action activities (PTK) in the form of initial reflection activities and conducting observations to identify problems that occur in the classroom, planning learning, implementing actions, observation and reflection. The findings of this CAR are: 1) Increased learning outcomes from the complete cycle I as many as 24 people or 72.7% to as many as 29 people who completed or 87.9%; 2) Improving science process skills from cycle I from 5 groups from 4 aspects assessed by 3 aspects, namely observing, collecting data and concluding still in sufficient category while in communicating aspect it is in good category.Keywords: Models, Guided Inquiry, Science Process Skills